1988
DOI: 10.1177/000331978803900406
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-Wave Doppler of Vertebral Arteries in Noninvasive Diagnosis and Management of Vertebro-Basilar TIAs

Abstract: Continuous-wave Doppler and angiography of the vertebro-basilar system were used in 38 patients with vertebro-basilar transient ischemic attacks. 63 vertebral arteries were studied. Among 47 normal Doppler parameters, 46 were confirmed by angiography. The sonographic diagnostic procedure showed a very high negative predictive value (97.87%), while the positive predictive value was relatively low (56.25%). Data from literature were reviewed. The authors suggest that when Doppler of vertebral arteries is negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Previous studies that compared Doppler velocimetry of vertebral arteries with arteriography indicated that Doppler had high sensitivity and specificity in examining the patency of vertebral arteries with the head in the neutral position. [11][12][13][14] Another study 15 that compared Doppler velocimetry with color duplex sonography indicated that the former had high validity (k = 1.00) in determining rotational stenosis of vertebral arteries. Haynes et al 16 found that the Doppler technique also displayed high interexaminer reliability (k = 0.68).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that compared Doppler velocimetry of vertebral arteries with arteriography indicated that Doppler had high sensitivity and specificity in examining the patency of vertebral arteries with the head in the neutral position. [11][12][13][14] Another study 15 that compared Doppler velocimetry with color duplex sonography indicated that the former had high validity (k = 1.00) in determining rotational stenosis of vertebral arteries. Haynes et al 16 found that the Doppler technique also displayed high interexaminer reliability (k = 0.68).…”
Section: Discussionmentioning
confidence: 99%